City of the dammed. Lima in the late eighties cinema and beginning of the nineties - Bustamante, Emilio (2009)
The article examines the representation of Lima as a sinister, prisonlike and grim environment in three peruvian movies from the end of the eighties and beginning of the nineties: Juliana (1989), Caídos del cielo (1990) and Alias La Gringa (1991). This illustration is then related to the political, econom - ic and social context on which the films were produced.